2019
DOI: 10.1038/s41598-019-49548-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative adipose transcriptome analysis digs out genes related to fat deposition in two pig breeds

Abstract: Fatness traits are important in pigs because of their implications for fattening efficiency, meat quality, reproductive performance and immunity. Songliao black pigs and Landrace pigs show important differences in production and meat quality traits, including fatness and muscle growth. Therefore, we used a high-throughput massively parallel RNA-seq approach to identify genes differentially expressed in backfat tissue between these two breeds (six pigs in each). An average of 37.87 million reads were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 62 publications
4
28
5
Order By: Relevance
“…The KEGG results showed that the meaningful pathways were mostly concentrated on glucose metabolism. Some of these pathways, such as 'Glycolysis / Gluconeogenesis,' were also found in a previous study by our team [44] . Although they are not directly related to lipid synthesis and metabolism, glucose and lipids can change into each other and participate together in the tricarboxylic acid cycle.…”
Section: Discussionsupporting
confidence: 76%
“…The KEGG results showed that the meaningful pathways were mostly concentrated on glucose metabolism. Some of these pathways, such as 'Glycolysis / Gluconeogenesis,' were also found in a previous study by our team [44] . Although they are not directly related to lipid synthesis and metabolism, glucose and lipids can change into each other and participate together in the tricarboxylic acid cycle.…”
Section: Discussionsupporting
confidence: 76%
“…Two genes substantially influenced by Trim28 adi-KO were Olr1 (oxidized low density lipoprotein receptor 1) and Klf14 , both of which have been previously implicated in adipocyte function 18 25 . We demonstrated a 30–40-fold increase in Olr1 gene expression in both male and female adi-KO mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, studies from Olr1-KO mice have demonstrated inhibition of de novo lipogenesis via reductions in expression of fatty acid synthase ( Fasn ), stearoyl-CoA desaturase ( Scd1 ), and ELOVL family member 6 ( Elovl6 ) 21 . Moreover, other studies have implicated Olr1 as a gene that regulates FM in several mammalian models 22 , 25 , and that its’ expression is regulated by PPARγ to control adipocyte cholesterol levels 20 . Thus, the substantial upregulation of Olr1 in adipose tissue of Trim28 adi-KO mice, could explain several aspects of the observed phenotype, particularly those related to alterations in the abundance of specific lipid species.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is stimulating ECM development [87] and the genes involved in ECM were enriched in Duroc than Iberian pigs [86]. In addition, genes involved in insulin signaling pathway and insulin resistance were upregulated in local Songliao pigs compared to in the Landrace pig breed [88]. Functional analysis of differentially expressed genes in the subcutaneous adipose tissue indicated upregulation of lipogenic and adipogenic processes, while processes associated with lipid mobilization and expenditure were downregulated in local breeds compared to modern breeds.…”
Section: Comparison Of Mrna Transcriptome Of Subcutaneous Adipose Tissuementioning
confidence: 99%